Incidence of ICT on service quality perception in grocery stores of Merida, Yucatan, Mexico - Polanco Carrillo, Pastor Alejandro (2022)
The objective of this research is to analyze the incidence of the use of Information and Communication Technologies (ICT) in the perception of quality in the service by customers of grocery stores in the west of the city of Mérida, Yucatán, Mexico. Faced with a highly competitive and changing market, one of the main threats faced by grocery stores is the limited vision that the owners have regarding the innovation and implementation of ICTs within the business, taking into account the direct competition they have with convenience stores, which offer the same products, but differ in additional services (24-hour service, deposits, recharges, payment facilities through bank terminals, payment for services such as water, electricity, internet, among others). With a quantitative and cross-sectional approach through the use of a sample of 282 people, the perception of customers was measured using the service quality model called Retail Service Quality Scale (RSQS), with a total of 23 divided questions in two sections (service quality and ICT). The results are a reliable sample of the positive impact of the use of ICT in grocery stores and the perception of quality in the global service, in the same way, customers express a high degree of satisfaction with the service received.